The Hots Crisis in Geography Classroom: Analysis of Factors Causing Low C4 Ability of High School Students - Rana; Ahyuni; Saiful Adli bin Suhadak (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Analytical skills (C4) are an essential part of Higher Order Thinking Skills (HOTS), which is the main requirement in the Merdeka Curriculum. However, students’ analytical abilities in the material on Village and City Spatial Interaction remain low. This study aims to identify the factors that cause the low analytical ability of grade XII students at SMA Negeri 3 Bukittinggi. The research method uses a mixed-methods approach, combining quantitative analysis of students’ daily test results based on HOTS essay questions and qualitative analysis through questionnaires and interviews to explore the causal factors. A total of 132 students were analyzed for the ability category, and 20 were purposively selected for in-depth qualitative data collection. The results showed that 86% of students were in the Not Comprehending category, characterized by descriptive, non-concept-based answers. The main findings revealed that low analytical ability was caused by weak mastery of the geography concept, a lack of familiarity with HOTS questions, the absence of an analytical assessment rubric, and a learning process still oriented towards memorization. Conceptual models derived from data synthesis indicate that weak conceptual input and non-HOTS-oriented learning directly affect the low quality of student analysis. This research emphasizes the need to strengthen concept-based learning and improve the application of HOTS questions to enable students’ analytical skills to develop optimally.